Revisão taxonômica do grupo Nigricornis Conura Spinola (hymenoptera, Chalcididae) - Silva, Janaína Pissinate (2017)
A review of the group nigricornis of Conura Spinola (Chalcididae, Hymenoptera) is presented. 22 species were found, eight of which were unpublished and 14 previously described, namely: Conura azteca (Cresson, 1872), C. conjungens (Walker, 1871), C. coxalis (Cresson, 1872), C. flavoaxillaris (Ashmead, 1904), C. koehleri (Blanchard, 1935), C. lasnierii (Guérin, 1845), C. martinezi Delvare, 1993, C. montezuma (Cresson, 1872), C. nigricornis (Fabricius, 1798), C. nortoni, 1872), C. pompiloides (Walker, 1871), C. rufa (Gahan, 1934), C. sibinecola (Blanchard, 1934) and C. silvestrii (Ashmead, 1904). The following synonyms will be proposed: C. napo Delvare, 1993 as a junior synonym of C. sibinecola and C. phobetronae Delvare, 1993 as synonymous with C. martinezi. Considerations on the identity of C. coccinea (Cresson, 1865) are presented. The diagnostic characters of the group are discussed and a diagnosis is re-presented. Unpublished records of host genera and species, including the Erebidae family (Lepidoptera), are also presented. All species of the group are redescribed or described, and organized into identification keys.